Late arrival: recruiting coreceptors to the T cell receptor complex. - Van Der Merwe, P; Cordoba, S (2011)
In this issue of Immunity, Jiang et al. (2011) provide evidence that the CD8 coreceptor is recruited to the T cell receptor (TCR) complex after initial TCR triggering where it stabilizes the TCR-peptide-major histocompatibility complex interaction.